Pengaruh Kompetensi Digital dan Strategi SDM terhadap Kinerja Bisnis Lestari Homestay Jimbaran - I Putu Dony Indrayana (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Abstract This study aims to analyze the influence of digital competence and human resource (HR) strategies on the business performance of Lestari Homestay Jimbaran. This study uses a qualitative approach with a descriptive research type. Data were collected through interviews, observations, and documentation. Data analysis techniques use SWOT analysis. The results show that digital competence and HR strategies play an important role in improving homestay business performance. Digital competence is reflected in the ability to manage social media, utilize online booking platforms, Google Maps, and digital communication through WhatsApp Business. HR strategies are implemented through employee capability development, service quality improvement, and adaptation to digital technology. The main strengths lie in responsive service, strategic location, and digital adaptability, while weaknesses include limited human resources and suboptimal digital content management. Opportunities arise from increasing tourist arrivals in Bali, while threats come from intense competition among accommodation businesses. Digital competence and HR strategies have proven to improve business visibility, customer loyalty, and homestay business performance.